Aplicaciones de SIG y teledetección en la exploración de patrones arqueológicos en el ámbito geográfico del Gran Coclé - Chantada Acosta, José Ramón; Casciani Sicardi, Mercedes (Revista Española de Antropología Americana, 2007)
The prime object for using the GIS and remote method detections, which we are applying in the archaeological project, is to find the links between archaeological items on the geographic space in relation to their location, and in this way justify the differential cultural activities as part of the landscape of the plains and mountains of Coclé. In Panamá there is not enough qualified cartographic and thematic maps. For this reason we need to improve all the geographical information using high resolution remote images and digital models of the landscape. This gives us a complete mapping of the area which helps us to understand the past, and try to arrange the present and manage the historical and cultural resources of the panamenian patrimony that requires a serious and commitment scope with projection.